ENDOGENEITY TESTING: HEURISTIC BEHAVIOR AS A REFERENCE FOR BEGINNING INVESTORS IN MAKING INVESTMENT DECISIONS - Syailendra Eka Saputra; Fajri Adrianto; Mohamad Fany Alfarisi; Masyhuri Hamidi; Fajri Muharja (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This study aims to examine the tendency of endogeneity on heuristic behavior as a reference for novice investors in making investment decisions. Endogeneity is a deviation in OLS modeling which shows that there is still a correlation between the independent variables in the model and the error, causing biased results. The issue of endogeneity is an interesting aspect of current research, and still creates pros and cons for researchers in the fields of finance and econometrics. In this study, 158 respondents were used who were novice investors. The selection of respondents was done randomly. In this study, four categories of variables were used, namely the dependent variable, namely investment decisions, the independent variable, namely financial risk tolerance, endogenous heuristic behavior variables and financial literacy instrument variables. The analysis method is carried out using ivregress 2sls which is processed with Stata. The test results found that endogeneity symptoms were detected in heuristic behavior of novice investors. This behavior appears and influences investment decisions because it is preceded by financial literacy, which rejects the insights that investors have about financial science or investment.